Pengaruh Pelatihan Terhadap Peningkatan Kreativitas Melalui Peningkatan Kompetensi Tenaga Pendidik Dengan Berbasis Teknologi STEAM: Studi Pada Peserta Pelatihan Tahun 2021-2022 Kabupaten Ciamis - Fikri Fauzan Dzikri (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The background of this research is because there are problems that have been identified as follows. Teaching staff cannot create new innovations in learning. Teaching staff cannot collaborate on something that can create something interesting in learning. Cannot create a pleasant learning atmosphere. The low use of learning media in the teaching process. In this case, according to the results of interviews with the head of the Ciamis District education office, learning still uses a simple method. So it does not increase student enthusiasm in learning. Thus, the purpose of this study was to determine the effect of training on increasing the creativity of educators through competence development based on STEAM technology for training participants in 2021-2022, Ciamis Regency. The method used is descriptive and verification research methods. The results of the study show that training has a positive and significant effect on increasing the creativity of educators based on STEAM technology for training participants in 2021-2022 in Ciamis Regency, meaning that if the training is carried out continuously, the creativity of educators will increase. Increasing competence has a positive and significant effect on increasing the creativity of educators based on STEAM technology for training participants in 2021-2022 in Ciamis Regency, meaning that if competency improvement is carried out continuously, the creativity of educators will increase. Training has a positive and significant effect on increasing the creativity of educators through increasing competency based on STEAM technology for training participants in 2021-2022, Ciamis Regency. This means that if the training is carried out with an increase in competence, then the creativity of the teaching staff will also increase.